Differential coping strategies exerted by biofilm and planktonic cells of Bacillus subtilis in response to a protozoan predator - Kolodkin-Gal, Ilana; Murugan, Prem Anand; Mahapatra, Smruti; Zanditenas, Eva; Ankri, Serge (Microbiology spectrum, 2025)
The human protozoan parasite Entamoeba histolytica feeds on intestinal microbiota to survive. To enhance the effectiveness of probiotics, we characterized how they respond to amoeba predators. We found that probiotics decrease the expression of biofilm-related genes to avoid predation while simultaneously inducing their stress response and increasing their motility. Our results can provide novel directions for engineering probiotic bacteria to overcome gastrointestinal-associated parasitic diseases. Additionally, it highlights a fundamental mechanism through which bacterial prey can evade predation in the gastrointestinal tract.